(untitled) (Semiárida, 2021)
The aim of this work was to classify, from local climate data, the climate of the north, center and south of the agricultural area of La Pampa province using the Köppen and the Thornthwaite climate classification. The meteorological temperature records from 1941 to 2010 of General Pico (northern agricultural region) and Santa Rosa (central agricultural region), and from 1941 to 1970 of Guatraché (southern agricultural region) and the precipitation records from 1980 to 2018 were used. Different soil water stores were also used according to the type, texture and depth of soil present in each locality. According to the Köppen climate classification, the climate is the same in all locations studied. The climate of the agricultural area of La Pampa is "temperate without dry season with hot summer (Cfa)". According to the climate classification of Thornthwaite, the climate of the north of the agricultural area of La Pampa (General Pico) is humid subhumid, with no or small water deficit, cold temperate mesothermal with a summer concentration of thermal efficiency less than 48 % (C2rB´2a´). The climate of the center and south of the agricultural area (Santa Rosa and Guatraché) is dry subhumid, with little or no excess water, cold temperate mesothermal with a summer concentration of thermal efficiency less than 48 % (C1rB´2a´). The type of climate in the three studied localities was the same for the different water storage used according to the soil. The Thornthwaite climatic classification was able to differentiate two types of climate from the hydrological point of view in the agricultural area of La Pampa statistical analysis of precipitation. It is expected that, this study will be a bibliographic reference for the field works, developed in the agricultural area of La Pampa, that require classify the climate of the place where they were carried out. inaccordance with the